COVID-19, Governments’ Response and the Feminisation of Poverty: Ekiti State, Nigeria in Perspective (Interdisciplinary Journal of Education Research, 2020)
This article examined the effects of the Corona Virus Disease (COVID-19), and governments’ response action on female poverty in Ekiti State, Nigeria. Discourse on female poverty abounds, but there is the need to revisit the topic, particularly in the light of a global pandemic. Qualitative research approach was adopted. The method combined the use of primary data through the conduct of Key informants Interview, and the review of secondary materials to generate data. Ekiti State was purposively selected, while Ekiti Central Senatorial District was conveniently selected from the three Senatorial Districts being the seat of commerce of the State. Three towns from three Local Government Areas under Ekiti Central: Adebayo, (Ado Ekiti); Aramoko (Ekiti West); and Ipoti (Ijero) were randomly selected. A total of seven women, including traders/artisans who are breadwinners of their respective families, were interviewed. Responses were analysed thematically and with the use of the descriptive method. It was found-out that governments’ lockdown measure had a negative effect on commercial activities, as those activities were restricted; an action which had a multiplier effect on female/household poverty. Despite the punitive measures attached to the disobedience of the lockdown order, many women still engaged in ‘illicit’ commercial activities, as a desperate move to feed their respective families. Besides, the palliative provided by the government to cushion the effect of the lockdown was limited to grossly inadequate food items. The paper recommends that government should put in place a social security scheme such as an emergency fund.
Keywords: COVID-19; Governments’ response; Feminisation of poverty